2021
DOI: 10.3390/ijerph18115932
|View full text |Cite
|
Sign up to set email alerts
|

Application of EN 16615 (4-Field Test) for the Evaluation of the Antimicrobial Activity of the Selected Commercial and Self-Made Disinfectant Wipes

Abstract: The purpose of disinfectants is to reduce microorganisms on a contaminated surface and to prevent the spread of microorganisms. The relatively new EN 16615 simulates disinfection by wiping and allows for assessing the recovery of microorganisms from the surface and, importantly, the degree of spread of microorganisms when the surface is disinfected by wiping. For the first time, using this standard, the tested products in the form of commercial disinfectant wipes were compared with self-made wipes soaked in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Only QAC3 was able to achieve an average 5-log reduction under the testing conditions used in this study; even then, this was only achieved against P. aeruginosa, not S. aureus. This discrepancy in performance under the novel testing conditions is not surprising, as this has been seen previously in the literature when testing commercial disinfectant towelette products under conditions more re ective of realistic use [23,31]. Further, others [32] have found that the method used to test disinfectant e cacy results in signi cant differences in performance.…”
Section: Discussionmentioning
confidence: 52%
“…Only QAC3 was able to achieve an average 5-log reduction under the testing conditions used in this study; even then, this was only achieved against P. aeruginosa, not S. aureus. This discrepancy in performance under the novel testing conditions is not surprising, as this has been seen previously in the literature when testing commercial disinfectant towelette products under conditions more re ective of realistic use [23,31]. Further, others [32] have found that the method used to test disinfectant e cacy results in signi cant differences in performance.…”
Section: Discussionmentioning
confidence: 52%
“…Only QAC3 was able to achieve an average 5-log reduction under the testing conditions used in this study; even then, this was only achieved against P. aeruginosa , not S. aureus. This discrepancy in performance under the novel testing conditions is not surprising, as this has been seen previously in the literature when testing commercial disinfectant towelette products under conditions more reflective of realistic use [ 23 , 31 ]. Further, others [ 32 ] have found that the method used to test disinfectant efficacy results in significant differences in performance.…”
Section: Discussionmentioning
confidence: 57%